THE USE OF AI-POWERED TOOLS IN ENGLISH WRITING INSTRUCTION FOR UZBEK UNDERGRADUATES (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The integration of Artificial Intelligence (AI) into language education has transformed traditional pedagogical approaches, particularly in the area of writing instruction. For Uzbek undergraduates studying English, AI-powered tools provide support in grammar correction, vocabulary enhancement, coherence development, and content generation. This paper explores how AI-driven platforms can be effectively utilized to support the development of academic and creative writing skills, examines their benefits and limitations, and offers practical recommendations for educators in Uzbekistan..